Linear Cryptanalysis of Modified SAFER + Algorithm - Melsik K. Kyureghyan; Knarik M. Kyuregyan (Изд-во НАН РА)
In paper [1] a modified SAFER+ [2] algorithm was presented. It was shown that those modifications made it possible to speed up a modified algorithm implementation about 1,7 times and obtain the same security level as compared with SAFER+ in terms of differential analysis. In this paper a linear cryptanalysis of modified SAFER+ algorithm is presented and it is shown that it has the same resistance against linear cryptanalysis as compared with an original SAFER+.
Keywords: Mathematics; Algorithm